PROGRAM PEMBANGUNAN DAN PEMBERDAYAAN MASYARAKAT DESA (P3MD) DI DESA PULAU GADANG KECAMATAN XIII KOTO KAMPAR - Irma Yuni; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The Village Community Development and Empowerment Program (P3MD) is a program of the central government through the village ministry which is implemented by the village administration and the village community. In the village community empowerment program in Pulau Gadang Village there is still a lack of understanding of the village community in developing the catfish culture business. The concept used is Mardikanto's theory in Theresia, namely the process of community empowerment is a process of capacity building: human capacity development, business capacity development, environmental capacity development, and institutional capacity development. This study uses qualitative research with a descriptive approach and the required data both primary and secondary obtained through observation, interviews and documentation techniques for further analysis using purposive sampling techniques and snowball procedures. The results of this study indicate that: first, the activities of the community empowerment program in Pulau Gadang Village District XIII Koto Kampar are already running but not yet optimal Second, the factors that hampered community empowerment program activities in Pualu Gadang Village, XIII Koto Kampar Subdistrict were natural conditions, human resources, and facilities and infrastructure.Keywords: Program, P3MD, Community Empowerment